Pengaruh Kemudahan Penggunaan Dan Promosi Terhadap Keputusan Penggunaan Uang Elektronik (Studi Kasus Di Gopay Pada Mahasiswa S1 dan D3 Fakultas Ekonomi dan Bisnis Universitas Muhamadiyah Metro) - Jaya, Andri; Suharto, Suharto (Jurnal Manajemen DIVERSIFIKASI, 2021)
Jaya, Andri: 2020. EFFECCT OF EASE OF USE AND PROMOTION TO DECISION TO USE ELECTRONIC MONEY (case on Gopay in college student S1 and D3 Faculty of Economics and Business Muhamadiah University Metro. Advisor (I) Suwarto,S.E.,M.M. dan Advisor (II) SRI RETNANING RAHAYU,S.E,.M.M. This research is focused on: ease of use and promotion to decision to use electronic money, the goal want to adviced by reseacher is to know do ease of use and promotion have any effect to decision to use electronic money Gopay in colege student of FEB Muhamadiah university Metro. the method used is descriptive quantitative, with a population of FEB students are still active , with totalling 1174 students. The sampling technique uses purposive sampling and the sample is based on the Slovin formula so, there are 92 respondents in this research. The results obtained from ease of use, and promotion on decision to use se electronic money Gopay: case studies on FEB UM Metro students are based on the calculation of multiple linear regression tests that the variable ease of use (X1) is positive and significant effect on decision to use electronic money Gopay, promotion variable (X2) is not positive and significant effect on decision to use electronic money Gopay,.Based on the f test (Simultaneous) of ease of use, and promotion variable, simultaneously have a significant influence on decision to use electronic money Gopay There is a positive and significant relationship between the independent variable and the dependent variable. It means that if the independent variable increases, the dependent variable also increases. Keywords: Ease Of Use, Promotion and decision to use